1999
DOI: 10.5694/j.1326-5377.1999.tb123691.x
|View full text |Cite
|
Sign up to set email alerts
|

Erectile dysfunction in the community: a prevalence study

Abstract: Objective To investigate the prevalence of erectile dysfunction (ED) in the South Australian community, and the influence of demographic and other risk factors. Design Survey by mailed questionnaire (based on the University of California, Los Angeles prostate cancer index) of a subset (men who agreed to participate) of a probability sample of the South Australian community who completed a multiuser interview survey. Participants and setting Men over the age of 40 in South Australia. Main outcome measures Sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 16 publications
7
53
1
5
Order By: Relevance
“…Whether this is related to a genuine underlying biological mechanism such as that mediated by alteration in sex hormone metabolism in smokers [28], although others have found no association [29], or whether it reflects indirectly the operation of other unrecognised health factors influencing both smoking status and PD, remains to be clarified. In contrast, evidence to suggest that smoking [20,30] and alcohol consumption [8] increase the risk of ED were not confirmed in this study. Alcohol consumption appears to have no independent effect on the range of reproductive health disorders examined in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Whether this is related to a genuine underlying biological mechanism such as that mediated by alteration in sex hormone metabolism in smokers [28], although others have found no association [29], or whether it reflects indirectly the operation of other unrecognised health factors influencing both smoking status and PD, remains to be clarified. In contrast, evidence to suggest that smoking [20,30] and alcohol consumption [8] increase the risk of ED were not confirmed in this study. Alcohol consumption appears to have no independent effect on the range of reproductive health disorders examined in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…Associations with cerebrovascular disease and hypertensive disease identified in age-adjusted analyses have been shown in other studies [3,20], although in our study these associations were reduced in multivariate analysis. Similarly, strong associations between LUTS and cardiovascular disease and treatment of hypertension have been demonstrated [34].…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…11,12,13 A cross-sectional study found that 22% of men visiting GPs in London had sexual difficulties. 15 Fatusi et al reported an overall prevalence rate of 43.8% among men living in some communities in Ile-Ife, Nigeria.…”
Section: Resultsmentioning
confidence: 99%
“…8,9 Though many prevalence studies have reported that ED is common in most communities, there is evidence that it is often under-diagnosed in primary care settings. 10,11,12,13,14 Clinicians at the primary care level certainly have an important role to play in the management of ED, since this setting allows early identification of affected individuals and prompt treatment or referral to specialist care. Since the majority of the Nigerian populace receive their health services at the primary care level, it is imperative to explore the role of the clinicians in this setting in the diagnosis and management of the disorder.…”
Section: Original Researchmentioning
confidence: 99%